Developing a multidimensional framework for wine tourist behavior: Evidence from Greece - Maria Alebaki; George Menexes; Alex Koutsouris (Wine Economics and Policy, 2015)
In response to the need for a better empirical understanding of the multiple factors that drive the demand of wine tourism, this paper serves a twofold objective: first, to test the distinctiveness of motivations for visiting a wine region along with a winery; and secondly, to explore whether geographical distance between tourists' place of origin and the wine region can add to the ability of other wine consumer/tourist variables (product involvement; product knowledge; wine tourist identity; past experience) to predict specific aspects of wine tourist behavior. In doing so, quantitative survey data were collected from 381 visitors of 12 wineries located in Northern Greece. Results from Principal Component and Multiple Hierarchical Regression Analyses indicate that travel distance predicts wine purchasing at the cellar door as well as the motivational factors associated with' Socialization' and "Destination attractiveness". Further, the study proposes a conceptual framework for wine tourism motivation.
Keywords: 330; Motivations; Travel distance; Wine tourism